Plant-driven Removal of Heavy Metals from Soil: Uptake, Translocation, Tolerance Mechanism, Challenges, and Future Perspectives - Sveta, Thakur; Singh, Lakhveer; Zularisam, A. W.; Muhammad Faisal, Siddiqui; Atnaw, Samson M.; Mohd Fadhil, Md Din (Springer International Publishing, 2016)
Increasing heavy metal (HM) concentrations in the soil have become a significant problem in the modern industrialized world due to several anthropogenic activities. Heavy metals (HMs) are non-biodegradable and have long biological half lives; thus, once entered in food chain, their concentrations keep on increasing through biomagnification. The increased concentrations of heavy metals ultimately pose threat on human life also. The one captivating solution for this problem is to use green plants for HM removal from soil and render it harmless and reusable. Although this green technology called phytoremediation has many advantages over conventional methods of HM removal from soils, there are also many challenges that need to be addressed before making this technique practically feasible and useful on a large scale. In this review, we discuss the mechanisms of HM uptake, transport, and plant tolerance mechanisms to cope with increased HM concentrations. This review article also comprehensively discusses the advantages, major challenges, and future perspectives of phytoremediation of heavy metals from the soil.